Immune Cells and Microbiota Response to Iron Starvation - Chieppa, Marcello; Giannelli, Gianluigi (Frontiers in Medicine, 2018)
Metal ions are essential for life on Earth, mostly as crucial components of all living organisms; indeed, they are necessary for bioenergetics functions as crucial redox catalysts. Due to the essential role of iron in biological processes, body iron content is finely regulated and is the battlefield of a tug-of-war between the host and the microbiota.